Cement composition and concrete
The cement composition, featuring a high content of fine blast furnace slag powder with low basicity, addresses the challenge of temperature cracking in concrete and enhances the utilization of low basicity blast furnace slag powders.
Patent Information
- Application Number
- JP2023168429
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-04-09
AI Technical Summary
Existing cement compositions struggle to effectively utilize low basicity blast furnace slag powders, leading to difficulties in producing concrete resistant to temperature cracking.
A cement composition containing cement and a fine blast furnace slag powder with a basicity of 1.70 or less, where the content of the fine blast furnace slag powder is greater than 60% by mass and less than 85% by mass.
The cement composition enables the production of concrete that is resistant to temperature cracking, while also promoting the effective utilization of low basicity blast furnace slag powders.
Smart Images

Figure 2025058471000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a cement composition and a concrete using the cement composition. [Background technology]
[0002] In the cement industry, ground granulated blast furnace slag, which is a by-product of the production of pig iron in a blast furnace, has traditionally been used as a cement admixture. Basicity is one of the indicators of the quality of ground granulated blast furnace slag as a cement admixture, and it is known that the higher the basicity, the higher the activity. The basicity of ground granulated blast furnace slag used as a cement admixture in Japan is usually 1.8 or more. It is said that blast furnace slag with a low basicity is difficult to use as a cement admixture, and most of it is used as earthwork materials such as roadbed materials after being crushed.
[0003] Patent Document 1 describes a mixed cement composition that contributes to the effective use of low-basicity blast furnace slag, which is made of cement clinker, gypsum, limestone, and Al. 2 O 3 The mixed cement composition includes blast furnace slag having a basicity Bu(7d) of 1.20 or less, calculated from the following formula (1) based on a chemical composition of the blast furnace slag, and a basicity Bu(28d) of 1.00 or less, calculated from the following formula (2). The blast furnace slag has an activity index A50(7d) of 63.5 to 96.5% at an age of 7 days, and an activity index A50(28d) of 86.5 to 111.0% at an age of 28 days. The total content of the limestone and the blast furnace slag is more than 5.0% by mass and 10.0% by mass or less, and the content of the blast furnace slag is 1 to 90% by mass based on the total amount of the limestone and the blast furnace slag. Bu(7d)=(CaO+0.43×MgO+0.28×Al 2 O 3 ) / SiO 2 -0.46×TiO 2-0.27×MnO...Equation (1) Bu(28d)=(CaO+0.42×MgO+0.16×Al 2 O 3 ) / SiO 2 -0.60×TiO 2 -0.14×MnO ··· Equation (2) [In formula (1) and formula (2), CaO, MgO, Al 2 O 3 , SiO 2 , TiO 2 indicates the content (mass%) of calcium oxide, magnesium oxide, aluminum oxide, silicon dioxide, titanium oxide, and manganese oxide in blast furnace slag, respectively. However, if the content of titanium oxide is 0.8 mass% or more, the content of titanium oxide is 0.8 mass%.] It is also described that the content of blast furnace slag in the mixed cement composition is 0.1 to 5.0 mass %. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2023-21389 A Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a cement composition which makes it possible to produce concrete which is less susceptible to thermal cracking by using ground granulated blast furnace slag having a low basicity (specifically, 1.70 or less). [Means for solving the problem]
[0006] As a result of intensive research into solving the above-mentioned problems, the present inventors have found that the above-mentioned object can be achieved by a powdered cement composition containing cement and ground granulated blast furnace slag having a basicity of 1.70 or less, wherein the content of the ground granulated blast furnace slag in the cement composition is more than 60 mass % and not more than 85 mass %, and have completed the present invention. That is, the present invention provides the following [1] to [4]. [1] A powdered cement composition comprising cement and ground granulated blast furnace slag, wherein the ground granulated blast furnace slag has a basicity of 1.70 or less as calculated from the following formula (1), and the content of the ground granulated blast furnace slag in the cement composition is greater than 60% by mass and less than 85% by mass. Basicity = (CaO + MgO + Al 2 O 3 ) / SiO 2 (1) (In the above formula (1), CaO, MgO, Al 2 O 3 , and SiO 2 are the CaO content, MgO content, and Al content in the ground granulated blast furnace slag, respectively. 2 O 3 and SiO 2 The content (mass%) of
[0007] [2] The cement composition according to [1], wherein the MgO content in the ground granulated blast furnace slag is less than 4.0 mass%. [3] Concrete comprising the cement composition according to [1] or [2] above, fine aggregate, coarse aggregate, and water. [4] A method for producing a hardened concrete body made of the concrete described in [3] above, comprising: a mixture preparation step of mixing the materials constituting the concrete to prepare a mixture; a casting step of casting the mixture into a formwork; and a demolding step of demolding the hardened mixture from the formwork after the mixture in the formwork has hardened to obtain the hardened concrete body, wherein each step from the mixture preparation step to the demolding step is carried out at a temperature of 25°C or higher. Effect of the Invention
[0008] According to the cement composition of the present invention, concrete that is resistant to thermal cracking can be produced by using ground granulated blast furnace slag having a low basicity (specifically, 1.70 or less). [Brief description of the drawings]
[0009] [Figure 1] 1A is a longitudinal side view and a lateral front view of a member made of Invar steel to be installed in a formwork in an embodiment. FIG. [Diagram 2] FIG. 2 is a plan view of an insulated curing tank for simulating the temperature history inside mass concrete in the embodiment, with the polystyrene foam lid removed. [Diagram 3] FIG. 3 is a cross-sectional view showing a state in which an insulated curing tank for simulating the temperature history inside mass concrete in the embodiment is covered with a polystyrene foam lid, and cut in a direction perpendicular to the axis of a member made of Invar steel at the position of line AA in FIG. 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The cement composition of the present invention is a powdered cement composition containing cement and ground granulated blast furnace slag, wherein the basicity of the ground granulated blast furnace slag calculated from the following formula (1) is 1.70 or less, and the content of the ground granulated blast furnace slag in the cement composition is more than 60 mass% and 85 mass% or less. Basicity = (CaO + MgO + Al2 O 3 ) / SiO 2 (1) (In the above formula (1), CaO, MgO, Al 2 O 3 , and SiO 2 are the CaO content, MgO content, and Al content in the ground granulated blast furnace slag, respectively. 2 O 3 and SiO 2 The content (mass%) of The details are explained below.
[0011] Examples of cements that can be used in the present invention include various types of Portland cements, such as ordinary Portland cement, high-early-strength Portland cement, moderate-heat Portland cement, low-heat Portland cement, and sulfate-resistant Portland cement, as well as mixed cements, such as blast-furnace cement, fly ash cement, and silica cement, alumina cement, and ecocement, etc. These may be used alone or in combination of two or more. Furthermore, when blast furnace cement is used as the cement, the ground granulated blast furnace slag contained in the blast furnace cement corresponds to the "ground granulated blast furnace slag" used in the present invention. In other words, only the cement contained in the blast furnace cement corresponds to the "cement" used in the present invention. Furthermore, the amount of ground granulated blast furnace slag contained in the blast furnace cement is not included in the amount of "cement" used in the present invention, but is included in the amount of "ground granulated blast furnace slag" used in the present invention. In addition, the SO in cement 3 From the viewpoint of making thermal cracking less likely to occur in concrete using the cement composition, the content of is preferably 4.0 mass % or less, more preferably 3.0 mass % or less, and particularly preferably 2.0 mass % or less. The cement content in the cement composition is preferably 15% by mass or more and less than 40% by mass, more preferably 17-35% by mass, more preferably 20% by mass or more and less than 30% by mass, and particularly preferably 22-27% by mass. If the content is 15% by mass or more, the strength development of the cement composition is further improved. If the content is less than 40% by mass, the amount of ground granulated blast furnace slag is relatively large, so that effective utilization of the ground granulated blast furnace slag can be further promoted.
[0012] The basicity of the ground granulated blast furnace slag used in the present invention, obtained from the above formula (1), is 1.70 or less, preferably 1.40 to 1.69, more preferably 1.50 to 1.68, even more preferably 1.55 to 1.67, and particularly preferably 1.60 to 1.66. If the basicity exceeds 1.70, concrete using the cement composition is likely to crack due to temperature. In addition, if the basicity is 1.40 or more, an excessive decrease in the early strength development of the cement composition can be prevented. The above formula (1) is a calculation formula for basicity specified in "JIS A 6206:2013 (ground granulated blast furnace slag for concrete)".
[0013] The content of ground granulated blast furnace slag in the cement composition is more than 60% by mass and not more than 85% by mass, preferably 65-83% by mass, more preferably more than 70% by mass and not more than 80% by mass, particularly preferably 73-78% by mass. If the content is 60% by mass or less, the amount of ground granulated blast furnace slag is small, so the low heat generation effect (effect of reducing heat of hydration) by using ground granulated blast furnace slag is small. If the content is more than 85% by mass, the amount of cement is relatively small, and the strength development of the cement composition is reduced.
[0014] The content of MgO in the ground granulated blast furnace slag is preferably less than 4.0% by mass, more preferably 0.1 to 3.0% by mass, even more preferably 0.5 to 2.0% by mass, still more preferably 0.8 to 1.8% by mass, and particularly preferably 1.0 to 1.5% by mass. If the content is less than 4.0% by mass, thermal cracking is less likely to occur in concrete using the cement composition. In addition, the SO 3 From the viewpoint of making thermal cracking less likely to occur in concrete using the cement composition, the content of is preferably 1.0 mass % or less, more preferably 0.5 mass % or less, and particularly preferably 0.2 mass % or less.
[0015] The Blaine specific surface area of the ground granulated blast furnace slag is preferably 3,000 to 5,500 cm 2 / g, more preferably 4,000 to 5,000 cm 2 / g, and particularly preferably 4,200 to 4,800 cm 2 / g. The above Blaine specific surface area is 3,000 cm 2 When the Blaine specific surface area is 5,500 cm / g or more, the strength development of the cement composition is further improved. 2 / g or less, the fluidity of the concrete before hardening is further improved.
[0016] The Blaine specific surface area of the cement composition is preferably 3,000 to 5,500 cm 2 / g, more preferably 3,100 to 4,000 cm 2 / g, and particularly preferably 3,200 to 3,500 cm 2 / g. The above Blaine specific surface area is 3,000 cm 2 When the Blaine specific surface area is 5,500 cm / g or more, the strength development of the cement composition is further improved. 2 / g or less, the fluidity of the concrete before hardening is further improved.
[0017] The cement composition may contain fly ash. From the viewpoint of early strength development and the like, the content of fly ash in the cement composition is preferably 20 mass % or less, more preferably 15 mass % or less, and particularly preferably 10 mass % or less. The cement composition may also contain other powdered materials as needed. Examples of other powdered materials that may be added as needed include various cement admixtures (mixtures) such as silica fume, limestone, and natural pozzolans. These may be used alone or in combination of two or more. The content of other powdery materials in the cement composition is preferably 20% by mass or less, more preferably 15% by mass or less, and particularly preferably 10% by mass or less.
[0018] The concrete of the present invention contains the above-mentioned cement composition, fine aggregate, coarse aggregate, and water. In this specification, the term "concrete" includes not only a completely hardened product, but also a fluid form before hardening. The fine aggregate is not particularly limited, and examples thereof include river sand, mountain sand, land sand, sea sand, crushed sand, silica sand, slag fine aggregate, lightweight fine aggregate, etc. These may be used alone or in combination of two or more. The unit amount of the fine aggregate is not particularly limited, and may be a general unit amount in concrete. For example, the unit amount is preferably 500 to 1,200 kg / m 3 , more preferably 600 to 1,100 kg / m 3 , particularly preferably 650 to 1,000 kg / m 3 It is.
[0019] The coarse aggregate is not particularly limited, and examples thereof include river gravel, mountain gravel, land gravel, sea gravel, crushed stone, slag coarse aggregate, lightweight coarse aggregate, etc. These may be used alone or in combination of two or more. The fine aggregate ratio of the concrete is preferably 20 to 60%, more preferably 25 to 55%, and particularly preferably 30 to 50%. If the fine aggregate ratio is within the above range, the workability and ease of molding of the concrete are improved. The fine aggregate ratio refers to the volume ratio of fine aggregate to the total amount of fine aggregate and coarse aggregate. In addition, the concrete of the present invention may contain various admixtures such as cement dispersants (water reducing agents, AE water reducing agents, high performance water reducing agents or high performance AE water reducing agents), AE agents, antifoaming agents, and shrinkage reducing agents, as necessary. When concrete is produced in a high-temperature environment (e.g., at a temperature of 25°C or higher) or when a hardened concrete body is used in a high-temperature environment (e.g., at a temperature of 25°C or higher), there is little need to improve the freeze-thaw resistance of the concrete, and from the viewpoint of reducing material costs, it is preferable that the concrete does not contain an air-entraining agent, air-entraining water-reducing agent, or high-performance air-entraining water-reducing agent.
[0020] The ratio of tensile stress to splitting tensile strength of the concrete of the present invention (tensile stress / splitting tensile strength) is preferably 0.55 or less, more preferably 0.01 to 0.54, even more preferably 0.10 to 0.52, and particularly preferably 0.20 to 0.50. If the ratio is 0.55 or less, thermal cracking of the concrete is less likely to occur. The concrete of the present invention is resistant to thermal cracking after hardening. In particular, even when the above-mentioned concrete is produced and the hardened concrete is used at a temperature (environment) of 25°C or higher (preferably 26°C or higher, more preferably 27°C or higher), thermal cracking is unlikely to occur in the hardened concrete, so the concrete of the present invention is suitable for use as mass concrete. Here, mass concrete means concrete with a thickness of 80 to 100 cm or more, or concrete with a thickness of 50 cm or more for walls with a restrained bottom end, according to the Standard Specifications for Concrete. Furthermore, the concrete of the present invention can be suitably used in high temperature environments such as tropical and subtropical regions.
[0021] An example of a method for producing a hardened body made of the concrete of the present invention using the concrete includes a mixture preparation step of mixing the materials that make up the concrete to prepare a mixture, a pouring step of pouring the mixture into a formwork, and a demolding step of demolding the hardened mixture from the formwork after the mixture in the formwork has hardened to obtain a hardened concrete body, and the steps from the mixture preparation step to the demolding step are carried out at a temperature of 25°C or higher. In the kneaded product preparation step, the method of kneading the materials is not particularly limited, and for example, the materials may be charged all at once into a mixer or the like and kneaded, or the materials constituting the cement composition may be charged into a mixer or the like and kneaded (mixed), and then other materials may be charged into the mixer or the like and kneaded. Also, cement clinker and blast furnace slag may be simultaneously ground, and then the resulting ground mixture and other materials may be charged into a mixer or the like and kneaded (mixed), or each material may be charged into a mixer or the like and kneaded (mixed) and ground at the same time. In the above-mentioned manufacturing method, each step from the kneaded mixture preparation step to the demolding step is carried out at a temperature of 25° C. or higher, preferably 26° C. or higher, and particularly preferably 27° C. or higher. According to the manufacturing method of the present invention, even when the concrete is manufactured at a temperature (environment) of 25° C. or higher, the temperature stress generated under high temperature history is small, and it is possible to manufacture a concrete that is less susceptible to thermal cracking. The upper limit of the above-mentioned temperature is not particularly limited, but is usually 70° C., preferably 50° C.
[0022] Prior to the above-mentioned kneaded product preparation step, a blast furnace slag selection step may be provided in which the ground granulated blast furnace slag to be used as a material for the cement composition is examined to see whether it satisfies the condition that the basicity is 1.70 or less, and if the ground granulated blast furnace slag satisfies the above-mentioned condition, the ground granulated blast furnace slag is selected as a material for the cement composition, and if the ground granulated blast furnace slag does not satisfy the above-mentioned condition, the ground granulated blast furnace slag is not selected as a material for the cement composition. In this step, the basicity is measured for each of at least one or more types of ground granulated blast furnace slag from different sources, etc., which are prepared in advance, and the ground granulated blast furnace slag that satisfies the condition that the basicity is 1.70 or less is used as a material for the cement composition, thereby making it possible to obtain a hardened concrete body made of the concrete of the present invention. EXAMPLES
[0023] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. [Materials used] (1) Cement: ordinary Portland cement manufactured by Taiheiyo Cement Corporation. Details are shown in Table 1. (2) Ground granulated blast furnace slag A (shown as "blast furnace slag A" in Table 3): Details are shown in Table 2. (3) Ground granulated blast furnace slag B (shown as "blast furnace slag B" in Table 3): Details are shown in Table 2. (4) Fine aggregate A: crushed stone powder, density 2.57 g / cm 3 (5) Fine aggregate B: natural sand, density 2.56g / cm 3 (6) Coarse aggregate: crushed stone, density 2.55g / cm 3 (7) Water reducing agent: Pozzolith Solutions, product name "Master Pozzolith R168" (8) High-performance water reducing agent A: Product name "Mastergranium SKY8703" manufactured by Pozzolith Solutions (9) High-performance water reducing agent B: Product name "Masterglenium ACE8538" manufactured by Pozzolith Solutions
[0024] The chemical compositions of cement and ground granulated blast furnace slag were measured in accordance with JIS R 5204:2019 (Method for fluorescent X-ray analysis of cement). In addition, the density, Blaine specific surface area, and basicity of the cement were measured in accordance with JIS A 5201:2015 (Physical testing methods for cement). The mineral composition of the cement was analyzed by the Rietveld method using an X-ray diffractometer (D8 ADVANCE, Bruker Japan) and analysis software (DIFFRAC plus TOPAS (Ver5.0), Bruker Japan). Specifically, the theoretical profiles of various minerals were fitted to the measured profiles obtained from the powder X-ray diffraction results to determine the content of each crystalline phase. Furthermore, the density, Blaine specific surface area, and basicity of the ground granulated blast furnace slag were measured in accordance with JIS A 6206:2013 (ground granulated blast furnace slag for concrete).
[0025] [Table 1]
[0026] [Table 2]
[0027] [Explanation of the insulated curing tank] A formwork in which members made of Invar steel are installed for preparing uniaxially restrained specimens used in the examples and comparative examples, and an insulated curing tank for curing concrete poured into the formwork while simulating the temperature history inside mass concrete will be described with reference to Figs. 1 to 3. The specimen molds 3a, 3b, and 3c for preparing uniaxially restrained specimens are molds with inner dimensions of 100×101×850 mm, in which members made of Invar steel are placed inside. The member 1 (corresponding to members 4a, 4b, and 4c described later) is composed of a rod-shaped body 1a made of Invar steel and a restraining end plate 1b made of Invar steel. The members 4a, 4b, and 4c installed in the specimen formworks 3a, 3b, and 3c have rod-shaped diameters of 26 mm, 15 mm, and 9.2 mm, respectively. The restraining steel ratios (ratio of the cross-sectional area of the rod-shaped body to the cross-sectional area of the concrete, expressed as a percentage) of the specimen formworks 3a, 3b, and 3c are 0.7, 1.7, and 5.7%, respectively. Embedded strain gauges 5a, 5b, and 5c are installed in the approximate center of the rod-shaped members 4a, 4b, and 4c. Wires 9 are connected to the strain gauges 5a, 5b, and 5c (not shown in FIG. 2) for transmitting data obtained by the strain gauges. The strength test form 3d was a cylindrical form with an inner diameter of 100 mm and a height of 200 mm. A total of six such forms were prepared. The linear expansion coefficient of the above Invar steel is 0.5×10 -6 / ℃, which is negligibly small. The Young's modulus of the above-mentioned Invar steel is 140,000 N / mm 2 It is.
[0028] The thermal insulation curing tank 10 includes polystyrene foam containers 2, 2b made of polystyrene foam, a polystyrene foam lid 2a made of polystyrene foam, a formwork for increasing heat generation 6, formworks for specimens 3a, 3b, 3c, and a formwork for strength test 3d. Note that the thermal insulation curing tank 10 uses the formworks for specimens 3a, 3b, 3c, and the formwork for strength test 3d with different conditions for the purpose of obtaining various specimens. The formwork for increasing heat generation 6 is for simulating the temperature history inside mass concrete by pouring concrete 7 into the formwork to increase the amount of concrete in the insulating curing space 10 and increase the heat generation amount. The formwork for increasing heat generation 6 is the same as the formwork for specimen 3a, 3b, 3c except for its length and without the installation of members made of Invar steel. Four heat generation increasing frames 6 are arranged inside the polystyrene foam container 2b. The specimen formworks 3a, 3b, and 3c are placed on top of the heat generation increase formwork 6 so that the direction perpendicular to the longitudinal direction of the heat generation increase formwork 6 coincides with the longitudinal direction of the specimen formworks 3a, 3b, and 3c. After concrete 8 is poured into the specimen formwork 3a, 3b, 3c and the strength test formwork 3d, the gap between the polystyrene foam container 2b and the formwork is filled with polystyrene foam beads, and then the polystyrene foam lid 2a is placed on the top of the specimen formwork 3a, 3b, 3c and the strength test formwork 3d.
[0029] [Example 1] Cement, ground granulated blast furnace slag A, fine aggregates A to B, and coarse aggregate in the unit amounts shown in Table 3 were charged into a forced twin-shaft mixer and dry mixed for 30 seconds. Next, a liquid mixture of water, water-reducing agent, high-performance water-reducing agent A, and high-performance water-reducing agent B was charged into the forced twin-shaft mixer and mixed for 90 seconds. After scraping off the mixed material adhering to the inner wall of the forced twin-shaft mixer, the mixture was further mixed for 90 seconds to prepare concrete. The amounts of the water reducing agent, the high performance water reducing agent A, and the high performance water reducing agent B per 100 parts by mass of the cement composition (a mixture of cement and ground granulated blast furnace slag A) were set to 0.4 parts by mass, 0.9 parts by mass, and 0.5 parts by mass, respectively. The above concrete was poured into the above-mentioned specimen formworks 3a, 3b, 3c, strength test formwork 3d, and heat generation increasing formworks 6 (4 pieces), and then the specimen formworks etc. were placed inside the above-mentioned insulated curing tank 10. After casting, the concrete was left to stand until its temperature became the same as the outside air temperature (27°C) (20 days). The temperature was measured by a thermocouple (not shown in Fig. 2) installed directly below the strain gauge 5b. For the specimen of the specimen formwork 3b (with rod-shaped bodies having a diameter of 15 mm), the tensile stress was calculated using the following method. In addition, the preparation of concrete was carried out in an environment of 27°C.
[0030] [Calculation of tensile stress] The tensile stress was calculated by a general calculation method. Specifically, after measuring the strain (εs) of the steel material (Invar steel), the following formula (2) is used: The tensile stress of the concrete (σc) was calculated. σc = -As / Ac × Es × εs (2) (In equation (2), σc is the tensile stress of concrete (stress generated in concrete), As is the cross-sectional area of the steel (Invar steel), Ac is the cross-sectional area of the concrete, Es is the elastic modulus of the steel (Invar steel), and εs is the strain of the steel (Invar steel).)
[0031] [Calculation of splitting tensile strength] The splitting tensile strength was measured in accordance with "JIA A 1113:2018 (Test method for splitting tensile strength of concrete)" using specimens obtained from the strength test formwork. Next, the stress strength ratio (tensile stress / splitting tensile strength) was calculated using the tensile stress of the specimen in the specimen formwork 3b and the above-mentioned splitting tensile strength. The smaller the stress-intensity ratio, the less likely thermal cracks are to occur.
[0032] [Comparative Example 1] A hardened concrete body was obtained in the same manner as in Example 1, except that the ground granulated blast furnace slag B was used instead of the ground granulated blast furnace slag A. The stress strength ratio was calculated in the same manner as in Example 1 for the test specimens removed from the test specimen formwork 3b (rod-shaped bodies having a diameter of 15 mm). The results are shown in Table 4.
[0033] [Table 3]
[0034] [Table 4]
[0035] From Table 4, it can be seen that the concrete of Example 1 has a smaller stress-strength ratio than the concrete of Comparative Example 1, and is less susceptible to thermal cracking. [Explanation of symbols]
[0036] 1. Materials 1a Rod-shaped body 1b Restraint end plate 2, 2b Styrofoam container 2a Styrofoam lid 3a, 3b, 3c Formwork for specimen 3D Strength Test Formwork 4a Part (Use a rod with a diameter of 26 mm) 4b Part (Use a rod-shaped object with a diameter of 15 mm) 4c Part (Use a rod with a diameter of 9.2 mm) 5a, 5b, 5c Strain gauges 6. Formwork for increasing heat generation 7, 8 Concrete 9 Wiring 10. Insulated curing tank
Claims
1. A powdered cement composition comprising cement and ground granulated blast furnace slag, The ground granulated blast furnace slag has a basicity of 1.70 or less, calculated from the following formula (1): A cement composition, characterized in that the content of ground granulated blast furnace slag in the cement composition is more than 60 mass % and 85 mass % or less. Basicity = (CaO + MgO + Al 2 O 3 ) / SiO 2 ...(1) (In the above formula (1), CaO, MgO, Al 2 O 3 , and SiO 2 respectively represent the CaO content, MgO content, and Al content in the ground granulated blast furnace slag. 2 O 3 and SiO 2 The content (mass%) of
2. 2. The cement composition according to claim 1, wherein the MgO content in the ground granulated blast furnace slag is less than 4.0 mass%.
3. 3. Concrete comprising the cement composition according to claim 1 or 2, fine aggregate, coarse aggregate, and water.
4. A method for producing a hardened concrete body made of the concrete according to claim 3 by using the concrete, comprising: A mixture preparation step of mixing the materials constituting the concrete to prepare a mixture; A casting step of casting the kneaded mixture into a formwork; A demolding step is included in which, after the kneaded material in the formwork has hardened, the hardened body of the kneaded material is demolded from the formwork to obtain the hardened concrete body; A method for producing a hardened concrete body, characterized in that each step from the above-mentioned kneaded mixture preparation step to the above-mentioned demolding step is carried out at a temperature of 25°C or higher.
Citation Information
Patent Citations
Mixed cement composition and method for producing same
JP2023021389A
Cited By
Cement composition and concrete
WO2026116309A1